2022
DOI: 10.1007/s12274-022-4265-y
|View full text |Cite
|
Sign up to set email alerts
|

Regulations of active moiety in single atom catalysts for electrochemical hydrogen evolution reaction

Abstract: Hydrogen production from water splitting using renewable electric energy is an interesting topic towards the carbon neutral future. Single atom catalysts (SACs) have emerged as a new frontier in the field of catalysis such as hydrogen evolution reaction (HER), owing to their intriguing properties like high activity and excellent chemical selectivity. The catalytic active moiety is often comprised of a single metal atom and its neighboring environment from the supports. Recent published reviews about electricdr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
125
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 310 publications
(125 citation statements)
references
References 131 publications
0
125
0
Order By: Relevance
“…[4,5] Evidently, single atom catalysts (SACs) are highly preferred for HER catalysis. [6,7] However, SACs tend to aggregate due to inherent high surface energy, thereby losing their unique structural properties as well as promising catalytic performance. [8,9] Thus, selecting suitable supports to stabilize the SACs with maximum metal utilization efficiency is critical for large-scale applications.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] Evidently, single atom catalysts (SACs) are highly preferred for HER catalysis. [6,7] However, SACs tend to aggregate due to inherent high surface energy, thereby losing their unique structural properties as well as promising catalytic performance. [8,9] Thus, selecting suitable supports to stabilize the SACs with maximum metal utilization efficiency is critical for large-scale applications.…”
Section: Introductionmentioning
confidence: 99%
“…Combining the previous experimental results and theoretically calculated ΔG H values, Rh-based nanomaterials may serve as a promising candidate for pH-universal HER electrocatalysts. [12,13] For example, Guo and his team reported the successful preparation of monodisperse Rh 2 P nanoparticles by the colloidal method, in which the nanoparticles showed excellent HER performance in a wide pH range. [14] In addition, Du et al used the laser ablation method to synthesize compressed RhO 2 clusters embedded in Rh nanoparticles; the impressive performance indicated that Rh-based noble metals are superior for alkaline HER.…”
Section: Introductionmentioning
confidence: 99%
“…The dicoordinated N atoms in tri‐s‐triazine motifs substituted by the O atoms lead to enhance the separation efficiency of photo‐generated charge carriers of CN and then promote the reaction [4a] . Recently, single‐atom catalysts have become a hot topic in the field of materials due to their abundant and well‐defined atomic sites for tuning the electronic structure of catalysts [4b–o] . The combination of single‐atom with semiconductor (e.g., CN) offers new opportunities to solve long‐term problems in the field of photocatalysis [4g–j] .…”
Section: Introductionmentioning
confidence: 99%